MTOR Inhibition: From Aging to Autism and Beyond. (26th November 2013) - Kaeberlein, Matt
Abstract : The mechanistic target of rapamycin (mTOR) is a highly conserved protein that regulates growth and proliferation in response to environmental and hormonal cues. Broadly speaking, organisms are constantly faced with the challenge of interpreting their environment and making a decision between "grow or do not grow." mTOR is a major component of the network that makes this decision at the cellular level and, to some extent, the tissue and organismal level as well. Although overly simplistic, this framework can be useful when considering the myriad functions ascribed to mTOR and the pleiotropic phenotypes associated with genetic or pharmacological modulation of mTOR signaling. In this review, I will consider mTOR function in this context and attempt to summarize and interpret the growing body of literature demonstrating interesting and varied effects of mTOR inhibitors. These include robust effects on a multitude of age-related parameters and pathologies, as well as several other processes not obviously linked to aging or age-related disease.